1988
DOI: 10.1136/bmj.297.6640.15
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of calcium and postmenopausal bone loss.

Abstract: The use of calcium supplements to prevent postmenopausal bone loss and hence osteoporosis is widespread, but the evidence for their efficacy, either alone or in combination with other treatments, is contradictory. Skeletal measurements and dietary intake of calcium were determined in 59 healthy postmenopausal women, most of whom were within five years of the menopause. No correlation was found between current intake of calcium and either total calcium in the body or the density of trabecular or cortical bone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…This is consistent with the findings of Matkovic et al [25] who suggested that calcium intake is important during linear skeletal growth but seems to have little effect on age-related bone loss. Our results furthermore agreed with those obtained earlier by our group and others, namely that calcium intake does not influence the postmenopausal bone loss [11,12,26,27]. As the postmenopausal bone loss was unaffected by a high calcium intake, the positive effect on BMC at menopause remained 12 years after.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with the findings of Matkovic et al [25] who suggested that calcium intake is important during linear skeletal growth but seems to have little effect on age-related bone loss. Our results furthermore agreed with those obtained earlier by our group and others, namely that calcium intake does not influence the postmenopausal bone loss [11,12,26,27]. As the postmenopausal bone loss was unaffected by a high calcium intake, the positive effect on BMC at menopause remained 12 years after.…”
Section: Discussionsupporting
confidence: 83%
“…The importance of reproductive history and lifestyle factors for bone mass and risk of osteoporosis is, however, not well established. Several studies have indicated that oral contraceptives, lactation, calcium intake, and physical activity have a positive influence on the skeleton [7][8][9], whereas others have not been able to confirm these relations [10][11][12]. Most of the studies have been carried out in a cross-sectional design and have in general failed to discriminate between the influence on the peak bone mass and the postmenopausal bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that other nutritional factors have been the more important determinants (5). Several cross-sectional and longitudinal studies could not discern a relationship between the dietary calcium intake and the rate of postmenopausal bone loss (6)(7)(8)(9). In contrast with dietary calcium intake, calcium supplementation has been shown to reduce postmenopausal cortical bone loss in a number of clinical trials, but the effect was small and considerably less than that of estrogen replacement therapy (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 96%
“…Riggs concluded that "These data do not support the hypothesis that insufficient dietary calcium is a major cause of bone loss in women" (Riggs et al, 1987, 979). J.C. Stevenson reached the same conclusion in 1988 after conducting a more limited study (Stevenson, 1988). Interestingly, Riggs continues to advise his patients to consume 1000 mg of calcium from dairy products daily, despite his research results, on the grounds that "the nutritional value in dairy products goes beyond calcium" (Science, 1986, 519-20).…”
Section: A Calcium and Osteoporosismentioning
confidence: 76%